2006
DOI: 10.1002/chem.200501393
|View full text |Cite
|
Sign up to set email alerts
|

o‐Nitrobenzyl Photolabile Protecting Groups with Red‐Shifted Absorption: Syntheses and Uncaging Cross‐Sections for One‐ and Two‐Photon Excitation

Abstract: We evaluated the o-nitrobenzyl platform for designing photolabile protecting groups with red-shifted absorption that could be photolyzed upon one- and two-photon excitation. Several synthetic pathways to build different conjugated o-nitrobenzyl backbones, as well as to vary the benzylic position, are reported. Relative to the reference 4,5-dimethoxy-2-nitrobenzyl group, several o-nitrobenzyl derivatives exhibit a large and red-shifted one-photon absorption within the near-UV range. Uncaging after one-photon ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
303
0
14

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(333 citation statements)
references
References 59 publications
16
303
0
14
Order By: Relevance
“…30 This moiety was chosen due to its capability of undergoing two-photon photolysis 37 (at 740nm the two-photon cross section δ u Φ u ≈ 0.01 to 0.03 GM 38 ) and its previous use in biological systems. 39 Upon two-photon excitation, PEGdiPDA cleaves between the NBE and acrylate functionalities, releasing modified PEG and polyacrylate chains with pendant PEG.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…30 This moiety was chosen due to its capability of undergoing two-photon photolysis 37 (at 740nm the two-photon cross section δ u Φ u ≈ 0.01 to 0.03 GM 38 ) and its previous use in biological systems. 39 Upon two-photon excitation, PEGdiPDA cleaves between the NBE and acrylate functionalities, releasing modified PEG and polyacrylate chains with pendant PEG.…”
Section: Resultsmentioning
confidence: 99%
“…Based on a statistical treatment of chain growth networks, the critical extent of cleavage (p c ) is dictated by the weight average number of crosslinks per polyacrylate 1 kinetic chain ( N = 20 for this system 33 ), such that pc=1N1. 41 The degradation reaction as a function of irradiation time ( t ) is modeled as a first-order process as previously described 38,42 : d[NBE]dt=ke[NBE] with…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several different o-NB groups have been reported [14][15][16] , and small modifications to the structure of the o-NB linker have a significant impact on the photolysis rate. 14 The benzylic position (photodegradation site) of o-NB groups can be primary or secondary (Chart 1a, R 1 = −H or R 1 = −CH 3 ). Additionally, the o-NB group may contain no other aromatic substituents (R 2 =R 3 =−H), one or two aryl ethers, or other substituents.…”
Section: Introductionmentioning
confidence: 99%
“…29 Moreover, recent studies reported that NVOC-based moieties are also sensitive to NIR light with slower degradation kinetics in comparison to UV-light irradiation. 30,31 In this study, a straightforward method will be reported to design photocleavable microcapsules by the introduction of NVOC units in the shell structure. For this purpose, an NVOC-based diisocyanate oligomer has been synthesized from a photolabile diol and toluene 2,4-diisocyanate (TDI) in a condensation polymerization and used for the synthesis of photocleavable polyurea microcapsules.…”
Section: Introductionmentioning
confidence: 99%